Barriers and facilitators for the implementation of exercise oncology provision in Germany: a multilevel, mixed-methods evaluation of the Network OnkoAktiv - Voland, Annelie; Lohmann, Annette; Ansmann, Lena; Wiskemann, Joachim (European journal of cancer care, 2023)
Background. Strong evidence supports the beneficial impact of exercise on cancer patients. However, the provision of exercise programs in Germany is highly heterogeneous. Therefore, the network OnkoAktiv (OA) enables patient consultations and referrals from coordinating regional OA centers (RE) into community-based exercise programs (CBEP). Objective. The aim of this study was to identify barriers and facilitators for the implementation of OA network structures from the perspective of RE and certified CBEP. Methods. This evaluation was executed in a sequential mixed methods design. We conducted 16 qualitative interviews with each leader in RE and the certified CBEP. Then, 89 certified CBEP were invited to a quantitative, cross-sectional survey. Results. We identified 11 facilitators each for RE and certified CBEP, 7 barriers for RE and 5 for certified CBEP. Barriers dealt with, for example, financing OA network structures, a lack of knowledge of exercise trainers, inadequate patient referral, and missing collaborations by healthcare professionals (HCPs). Most of the named facilitators were adequate internal organizational resources, support and reachability of OA staffs, and collaboration with HCPs. Conclusion. Our findings indicate different challenges for the implementation of OA network structures. Future implementation efforts should consider the evaluation of individual barriers and the development of specific solutions.
Gesehen am 13.06.2023